STUDIES ON THE VARIOUS ALLOMETRIC RELATIONSHIPS IN THE INTERTIDAL GREEN MUSSEL, PERNA VIRIDIS LINNAEUS OF ENNORE ESTUARY, MADRAS - Shafee, M S (Indian Journal of Fisheries, 2011)
Comparatively little attention has been paid to the ecology of the Indian green mussel, Perna viridis Linnaeus (= Mytilus viridis Linnaeus) despite its good potentiality for fishery all along the Indian coastal and estuarine regions. Ennore estuary, Madras, has a large population of these green mussels. Since the mussels play a major role in the functioning of this estuarine ecosystem, the present study on the relationships between various parameters of these bivalves would facilitate future works on secondary productivity.